Crimea: Transforming the Ukrainian Peninsula into a Russian Island. Issue 1 (2nd January 2016) - Petrov, Nikolai
Abstract : The accelerated integration of Crimea into Russia's state system illuminates the overall sociopolitical process in Russia. The process was largely improved, with various agencies each pursuing its own course of action. Some were formed on the basis of existing Ukrainian institutions, while others were created de novo. In some cases, locals were given senior positions, while in others the top posts were assigned to appointees from other regions who had no previous ties to Crimea. Overall, Moscow was careful to take into account local factors, such as the role of the Crimean Tatar population. The situation remains fluid, with many state institutions still subject to modification.